A frente marítima da área central de Fortaleza e a revalorização do projeto urbano como instrumento de intervenção - Fernandes, Francisco Ricardo Cavalcanti (2012)
The social changes derived from the new arrangements of the world economy over the past forty years have reflected greatly in the spatial structure of cities. For this reason we are seeing the emergence of new modes of interpretation of the territorial situation of the city and new forms of intervention which began to consider, as starting point, the existing city. In this process we witness the revaluation of urban design as a thinking and intervervention instrument in the scope of urban policies which attests to the need to assume joint actions between government and private initiative, that is, to an approximation between urban planning, urban design and the market economy. This new situation indicates the assertion that design is the major instrument in contemporary urban policy. Among the many possibilities opened up in contemporary urban policy context we highlighted, in this work, those that derived from the revaluation process of decaying or abandoned Downtown Areas and Waterfronts and from the perception of the existing potential in those areas in regard to the possibility of recovering cities aiming to it’s (re) integration into the global economy through tourist activity and by attracting businesses and events. The objective of this research is to situate the recent urban design revaluation process in Fortaleza with focus on the spatial cutout named Downtown Waterfront. This work seeks to demonstrate the hypothesis that the recent projects to Fortaleza’s waterfront are placed in the context of contemporary urban projects and seek to insert it in the international tourism panorama. Among these we highlighted the not executed project of Ceará State’s Conventions and Exhibitions Multifunctional Center, developed in 2002.